Platform Pembelajaran Online Berbasis Media Sosial Menggunakan Laravel - Widyastuty, Wiwiek; Kholifah, Desiana Nur; Jefi , Jefi; Rofiah, Syahbaniar (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
According to the World Population Review, in 2021 Indonesia is ranked 54th out of 78 countries included in the ranking of world education levels. This is what makes the author want to create a learning system independently. Since Covid-19, internet usage has continued to increase. Based on the Badan Pusat Statistika (BPS) as much as 78.18% in Indonesia increased after the Covid-19 pandemic. In this research a website-based learning social media system will be designed. By using the concept of social media, it is expected to increase the attractiveness of students to study at home. Students can use the platform like using social media in general. There are several features such as likes, comments, discussion forums between students and teachers. This website also functions as a forum for teachers to interact with students online. The research method used is a qualitative research method with data collection techniques through literature study, observation and interviews. From these results it can be concluded that this social learning website can be used as an alternative learning at home and make a solution for website-based school learning platforms.